A Feminist Stylistic Analysis of Ava Max’s “Kings & Queens” - Audrey, Nazzaura Kayla; Syafiq, Muhammad; Ginting, Grace Chelvia; Rangkuti, Rahmadsyah (Journal of Language Intelligence and Culture, 2026)
This research investigates the linguistic construction of feminist meanings in Ava Max's song "Kings & Queens," focusing on the restricted relevance of Sara Mills' feminist stylistics to current popular music lyrics. Instead of viewing empowerment as a thematic result, the research examines how particular linguistic selections convey gendered roles and power dynamics. Employing a descriptive qualitative method, the analysis implements Sara Mills' framework at three tiers: (1) word choice (e.g., gender-specific nouns and judgmental terms), (2) syntactic arrangements (e.g., distribution of agency and modality), and (3) discourse structures (e.g., placement of voice and intended audience). The results suggest that empowerment in the song is not only claimed but built through a deliberate redistribution of agency, with female references taking on roles usually designated for male authority. Moreover, metaphorical frameworks like monarchy ("queen," "throne") serve as both representations of authority and as rhetorical instruments that subvert traditional gender hierarchies. At the discourse level, the lyrics depict women as both narrators and collective subjects, thus complicating the binary of subject/object representation outlined in Mills' model. These findings indicate that modern pop lyrics can reshape feminist stylistic patterns by merging personal agency with group identity. The research enhances theoretical understanding by broadening feminist stylistics beyond conventional literary works and showing how popular music conversations address gender using complex linguistic techniques instead of explicit ideological assertions.